Key Phytochemicals and Biological Functions of Chuanxiong Rhizoma Against Ischemic Stroke: A Network Pharmacology and Experimental Assessment - Zeng, Peng; Yi, Yao; Su, Hong-Fei; Ye, Chao-Yuan; Sun, Yi-Wen; Zhou, Xin-Wen; Lu, Youming; Shi, Anbing; Tian, Qing (Frontiers in Pharmacology, 2021)
Presently, the treatment options for ischemic stroke (IS) are limited due to the complicated pathological process of the disease. Chuanxiong Rhizome (CR), also known as Conioselinum anthriscoides “Chuanxiong” (rhizome), is the most widely used traditional Chinese medicine for treating stroke. This study aimed to uncover the key phytochemicals and biological functions of CR against IS through a network pharmacology approach combining with IS pathophysiology analysis. We employed permanent unilateral common carotid artery ligation to construct a mouse model of global cerebral ischemia and found that cerebral ischemia injuries were improved after 7 days of gavage treatment of CR (1,300 mg/kg/day). CR exerts protective effects on neurons mainly by acting on targets related to synaptic structure, synaptic function, neuronal survival and neuronal growth. A total of 18 phytochemicals from CR based on UHPLC-MS/MS that corresponded to 85 anti-IS targets. Coniferyl ferulate, neocnidilide and ferulic acid were identified as the key phytochemicals of CR against IS. Its brain protective effects involve anti-inflammatory, anti-oxidative stress, and anti-cell death activities and improves blood circulation. Additionally, the two most important synergistic effects of CR phytochemicals in treating IS are prevention of infection and regulation of blood pressure. In brain samples of Sham mice, L-tryptophan and vanillin were detected, while L-tryptophan, gallic acid, vanillin and cryptochlorogenic acid were detected in IS mice by UHPLC–MS/MS. Our findings provide a pathophysiology relevant pharmacological basis for further researches on IS therapeutic drugs.